Arabidopsis tRNA-derived fragments as potential modulators of translation. Issue 8 (2nd August 2020) - Lalande, Stéphanie; Merret, Rémy; Salinas-Giegé, Thalia; Drouard, Laurence
ABSTRACT: Transfer RNA-derived fragments (tRFs) exist in all branches of life. They are involved in RNA degradation, regulation of gene expression, ribosome biogenesis. In archaebacteria, kinetoplastid, yeast, and human cells, they were also shown to regulate translation. In Arabidopsis, the tRFs population fluctuates under developmental or environmental conditions but their functions are yet poorly understood. Here, we show that populations of long (30–35 nt) or short (19–25 nt) tRFs produced from Arabidopsis tRNAs can inhibit in vitro translation of a reporter gene. Analysing a series of oligoribonucleotides mimicking natural tRFs, we demonstrate that only a limited set of tRFs possess the ability to affect protein synthesis. Out of a dozen of tRFs, only two deriving from tRNA Ala (AGC) and tRNA Asn (GUU) strongly attenuate translation in vitro . Contrary to human tRF(Ala), the 4 Gs present at the 5ʹ extremity of Arabidopsis tRF(Ala) are not implicated in this inhibition while the G18 and G19 residues are essential. Protein synthesis inhibition by tRFs does not require complementarity with the translated mRNA but, having the capability to be associated with polyribosomes, tRFs likely act as general modulation factors of the translation process in plants.